Analysis of the Effectiveness of Law Enforcement against Corruption Crimes - Salsabilla, Salisah (Siber International Journal of Advanced Law (SIJAL), 2024)
Corruption remains one of the most persistent and damaging crimes affecting governance, economic development, and public trust in Indonesia. This study analyzes the effectiveness of law enforcement in combating corruption crimes, focusing on regulatory frameworks, institutional performance, and practical challenges in enforcement. Using a normative juridical method, the research examines Indonesian anti-corruption laws, key cases, and institutional roles, particularly those of the Corruption Eradication Commission (KPK), the police, and the judiciary. Findings indicate that while Indonesia has made significant legal and institutional progress, various challenges-including legal loopholes, political interference, and limited resources-continue to hinder optimal enforcement. The study also highlights fluctuations in Indonesia’s Corruption Perceptions Index (CPI) over the past decade as a reflection of ongoing struggles. To enhance effectiveness, the study recommends strengthening legal provisions, boosting institutional capacities, and fostering a robust anti-corruption culture.